Presenting and Representing Environments - Humphrys, Graham; Williams, Michael; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2005)
The presentation and representation of the environment can be found in every academic discipline and is a subject of increasing attention by the media. Scientists use implicit strict codes that need to be clearly understood by users of their findings. Their approach can and often does clash with alternative environmental information available from other sources that dwell on subjective aesthetic, emotional and personal sensitivities. Historical and literary accounts emphasize subjective responses to the environment, frequently eschewing measurable and measured facts provided by scientific investigation. It is vital to understand how these sources are filtered by users and applied selectively for various purposes in taking practical decisions about environmental action, in a political context and for education purposes. The chapters in this volume exemplify these important matters and demonstrate their significance in the fields of environmental action, in political contexts and for environmental education.
Cross-Disciplines, Cross-Cultures: The Environment as Social Construction -- Environmentalism Qua Environmental Non-Government Organisations and the Contested Remapping of British Columbia’s Forests -- Re-Negotiating Science in Protected Areas: Grizzly Bear Conservation in the Southwest Yukon -- The Moorlands of England and Wales: Histories and Narratives -- Exploration Literature and the Canadian Environment: From Way-Finding to Ways of Representation and Reading -- Changing Public Participation and the Environment of Swansea East -- Sustaining Local Riverine Environments: The River Valleys Committee in Calgary, Alberta, Canada -- A Picnic in March: Media Coverage of Climate Change and Public Opinion in the United Kingdom -- Challenging the Negative Critique of Landscape -- Threatened Environments, Atrophying Cultures, Lacklustre Policies -- Sustaining Arctic Visions, Values and Ecosystems: Writing Inuit Identity, Reading Inuit Art in Cape Dorset, Nunavut -- Cultivating a New Cattle Culture: Lifelong Learning and Pasture Land Management -- Environmental Education and Lifelong Learning: Awareness to Action.
Keywords: Geography; Human geography; Environment; Geography, general; Human Geography; Environment, general